Measuring Left-Right Political Orientation: The Choice of Response Format - Martin Kroh (Public Opinion Quarterly, 2007)
Although left-right items are a standard tool of public opinion research, there is little agreement about the optimal response format. Two disputes can be identified in the literature: (1) whether to provide respondents with a small or large number of answer categories, and (2) whether or not to administer the response scale including a midpoint. This study evaluates the performance of the 101, 11, and 10-point left-right scales, which directly speak to the two disputed aspects of measuring the left-right dimension. Drawing on data from a split ballot multitrait multimethod experiment carried out in a methodological pretest to the German Socio-Economic Panel (SOEP), the analysis shows that the choice of a response format makes a difference in terms of data quality: the 11-point left-right scale produces the highest validity of left-right data closely followed by the 10-point scale. Moreover, an application from electoral research illustrates that the choice of response formats affects substantive interpretations about the nature of the left-right dimension. Since all three scales perform about equally well in terms of reliability and the ease of administration, the findings suggest that the 11-point left-right scale should be used in survey research.
Additional information: This is a pre-copy-editing, author-produced PDF of an article accepted for publication in Public Opinion Quarterly following peer review. The definitive publisher-authenticated version “Measuring Left-Right Political Orientation / Martin Kroh. In: Public Opinion Quarterly 71 (2007), 2, pp. 204-220” is available online at: http://dx.doi.org/10.1093/poq/nfm009
Keywords: 330; Statistische Methode; Theorie; Panel